Comparative analysis of prevalence of intimate partner violence against women in military and civilian communities in Abuja, Nigeria - Chimah CU; Adogu POU; Odeyemi K; Ilika AL (Dove Medical Press, 2015)
Carol Uzoamaka Chimah,1 Prosper Obunikem Uche Adogu,2 Kofoworola Odeyemi,3 Amobi Linus Ilika4 1Medical Department, Ministry of Defence Headquarters, Abuja, Nigeria; 2Department of Community Medicine and PHC, Nnamdi Azikiwe University/Nnamdi Azikiwe University Teaching Hospital, Nnewi, Nigeria; 3Department of Community Health, University of Lagos, Lagos, Nigeria Introduction: Intimate partner violence (IPV) occurs across the world, in various cultures, and affects people across societies irrespective of economic status or gender. Most data on IPV before World Health Organization multicountry study (WHOMCS) usually came from sources other than the military. Result of this study will contribute to the existing body of knowledge and may serve as a baseline for future studies in military populations. This study compares the prevalence of the different types of IPV against women in military and civilian communities in Abuja, Nigeria.Methods: Using a multistage sampling technique, 260 women who had intimate male partners were selected from military and civilian communities of Abuja. Collected data on personal characteristics and different types of IPV experienced were analyzed to demonstrate comparison of the association between the different forms of IPV and the respondents’ sociodemographic and partner characteristics in the two study populations using percentages and Χ-square statistics, and P-value was assumed to be significant at ≤0.05.Results: The prevalence of the four major types of IPV was higher among the military respondents than among civilians: controlling behavior, 37.1% versus 29.1%; emotional/psychological abuse, 42.4% versus 13.4%; physical abuse, 19.7% versus 5.9%, and sexual abuse, 9.2% versus 8.8%. Significantly more respondents from the military population (59 [45.4%]) compared to civilians (21 [19.4%]) were prevented by their partners from seeing their friends (P=0.000). The situation is reversed with regard to permission to seek health care for self, with civilians reporting a significantly higher prevalence (35 [32.4%]) than did military respondents (20 [15.4%]) (P=0.002). The military respondents were clearly at a higher risk of experiencing all the variants of emotional violence than the civilians (P=0.00). The commonest form of physical violence against women was “being slapped or having something thrown at them, that could hurt”, which was markedly higher in the military (43 [33.1%]) than in the civilian population (10 [9.3%]), (P<0.05).Conclusion: IPV is a significant public health problem in Abuja, and the military population is clearly at a higher risk of experiencing all forms of IPV compared to the civilian population. The military should encourage and finance research on effect of military operations and posttraumatic stress disorders on family relationships with a view of developing evidence-based treatment models for military personnel. Keywords: intimate partner violence, prevalence, military, civilian, women, Abuja, Nigeria